Utilization of Financial Resources and Development of School Facilities and Services for Students and Teachers of Esperanza National High School - Karlyn B. Rico, MAT (Randwick International of Education and Linguistics Science Journal, 2021)
This study is a descriptive correlational study which determined the impact of the utilization of financial resources on the development of school facilities and services for students and teachers. Teachers, Supreme Student Council (SSG) Officers, class mayors, student athletes, Parent-Teacher Association (PTA) Officers, disbursing officer, bookkeeper and supply officer were the respondents of this study. They gave a reliable information regarding the utilization of financial resources. Findings revealed that Maintence and Other Operating Expenses (MOOE), Special Education Fund (SEF) and other financial resources were well implemented and the development they have given to the school facilities and services for students and teachers was very satisfactory. Effective utilization of MOOE increased the positive perceptions of the respondents about the welfare and development of school facilities and services for students and teachers in terms of academic achievement and other school performance indicators. Thus, MOOE and SEF should be utilized according to the approved budget where the teachers, PTA officers and School Governing Council (SGC) members will be part of the budget hearing. School administrators should involve all the teachers and some stakeholders in budget planning and implementation and should follow the budget specifications in planning and implementation to avoid diversion of funds.